2014
DOI: 10.1590/s1982-56762014000500005
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of Fusarium oxysporum f. sp. phaseoli by Trichoderma harzianum and its use for common bean seed treatment

Abstract: Biological control of seed-borne pathogens has shown to enhance germination and physiological quality of seeds. The objectives of this study were to evaluate the in vitro antagonistic effect of five Trichoderma harzianum isolates (CEN287, CEN288, CEN289, CEN290, and CEN316) against Fusarium oxysporum f. sp. phaseoli (Foxy) and test its potential use in seed treatment. Initially, pathogen and antagonists were grown in paired cultures at 25ºC, from which samples were assessed using scanning electron microscopy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
17

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 22 publications
3
37
0
17
Order By: Relevance
“…Previous studies in the field ofexamining the effect of different concentrations of various antagonist microorganisms such as T. harzianum and Verticillium lecani (10³, 10⁴, and 10⁶the colony unit per ml of suspension used to provide the seed treatments) on soil borne fungal diseases' control in products, such as tomato, beans and radishes showed that the difference in the colony unit even 1,000 spores in the seed treatment could cause a significant difference in the incidence of Fusarium wilt disease (Leeman et al ., 1996;EliRafai et al, 2003;and Carvalho et al, 2014). Thus, the inference is made that the seed treatment has been significantly important to control vascular diseases such as Fusarium wilt compared to non-vascular diseases.…”
Section: Decrease In the Incidence Of Cucumber Fusarium Wilt In Varammentioning
confidence: 99%
“…Previous studies in the field ofexamining the effect of different concentrations of various antagonist microorganisms such as T. harzianum and Verticillium lecani (10³, 10⁴, and 10⁶the colony unit per ml of suspension used to provide the seed treatments) on soil borne fungal diseases' control in products, such as tomato, beans and radishes showed that the difference in the colony unit even 1,000 spores in the seed treatment could cause a significant difference in the incidence of Fusarium wilt disease (Leeman et al ., 1996;EliRafai et al, 2003;and Carvalho et al, 2014). Thus, the inference is made that the seed treatment has been significantly important to control vascular diseases such as Fusarium wilt compared to non-vascular diseases.…”
Section: Decrease In the Incidence Of Cucumber Fusarium Wilt In Varammentioning
confidence: 99%
“…Após sete dias, quando a colônia testemunha (patógeno sem antagonista) encontrava-se totalmente colonizada, tomaram-se as medidas de diâmetro das colônias de C. herbarum. Para obtenção das médias de crescimento do patógeno, considerou-se como 100% de crescimento, a área final ocupada pela testemunha (CARVALHO et al, 2014).…”
Section: Metabólitos Voláteisunclassified
“…As placas foram incubadas a 25ºC e fotoperíodo de 12 h, até completa colonização do meio pelo patógeno nas placas testemunhas. Tomaram-se, então, as medidas de diâmetros das colônias do patógeno, ao sétimo dia, as quais foram convertidas em percentagem conforme o item anterior (CARVALHO et al, 2014). Os experimentos com metabólitos voláteis e não voláteis termoestáveis foram conduzidos duas vezes, em delineamento inteiramente ao acaso (DIC), com quatro repetições para cada isolado de T. harzianum.…”
Section: Metabólitos Não Voláteis Termoestáveisunclassified
“…As an additional advantage, some isolates of Trichoderma may also act as plant growth promoters (Carvalho et al, 2011). Different T. harzianum isolates have effectively reduced the incidence of white mold and other diseases in several economically important crops, such as tomato (Abdullah et al, 2008) and common bean (Geraldine et al, 2013;Carvalho et al, 2014).…”
Section: Biological Control Of White Mold By Trichoderma Harzianum Inmentioning
confidence: 99%